2016
DOI: 10.1159/000452412
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HMGB1 in Pial Arteriole Dilating Reactivity following Subarachnoid Hemorrhage in Rats

Abstract: High-mobility group box 1 protein (HMGB1) has been implicated in inflammatory responses, and is also associated with cerebral vasospasm after subarachnoid hemorrhage (SAH). However, there are no direct evident links between HMGB1 and cerebral vasospasm. We therefore investigated the effects of HMGB1 on pial arteriole reactivity following SAH in rats. We initially found that SAH induced a significant decrease in pial arteriole dilating responses to sciatic nerve stimulation (SNS), hypercapnia (CO2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…Interestingly, a previous study reported that H 2 only improves neuronal apoptosis at 24 h after SAH, but not 48 h. However, the present study found significant improvements in neuronal apoptosis in the vmPFC, which was different from previous studies ( 10 , 25 ). As indicated by a previous study ( 49 ), 7 day post-SAH was the most severe period of cerebral vasospasm after SAH. In the present study, it was noted that there was no change of cerebral blood flow indicated by CBF-ASL after H 2 administration 7 day post-SAH, which was consistent with previous study ( 50 ).…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, a previous study reported that H 2 only improves neuronal apoptosis at 24 h after SAH, but not 48 h. However, the present study found significant improvements in neuronal apoptosis in the vmPFC, which was different from previous studies ( 10 , 25 ). As indicated by a previous study ( 49 ), 7 day post-SAH was the most severe period of cerebral vasospasm after SAH. In the present study, it was noted that there was no change of cerebral blood flow indicated by CBF-ASL after H 2 administration 7 day post-SAH, which was consistent with previous study ( 50 ).…”
Section: Discussionsupporting
confidence: 56%